THE EFFECT OF E-SERVICE QUALITY ON MODERATED BUYING DECISIONS WITH CUSTOMER SATISFACTION IN MALANG CITY TIX.ID APPLICATION USERS - Ilma, Maya Aulia; Sadewo, Mohammad Tio Pangku; Vania, Amelindha (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2022)
This study aims to see how much e-service quality influences buying decisions, as moderated by consumer satisfaction, among Malang users of the TIX.ID application. This study employs a data analysis method known as Moderating Regression Analysis (MRA) with the SPSS 16.0 application. The sample for this study was determined using a purposive sampling technique on TIX.ID application users were residing in Malang, totaling 140 respondents. The data collection technique was used to distribute questionnaires with a sample of 32 statements for each respondent. According to the study's findings, consumer satisfaction can moderate e-service quality, which influences the purchasing decisions of TIX.ID application users in Malang City